Agriculture and Seasonal Work - Features and Prospects - Orbán, Szabolcs Gergely; Szabados, György (International Journal of Engineering and Management Sciences, 2017)
In terms of employment specialities, certain sectors of agriculture may show quite a different picture. Especially the seasonal nature of employment, including day laborers and / daily work hireling nature deserves attention. In our country it has long tradition and can be directly linked to regional mobility and commuting trends since some people move near the western border to Austria for work. However, at the same time, near the eastern border, seasonal workers arrive from the East, which has an impact on the local labor markets, and for the lives of some settlements. In our study, we want to study and elaborate the specific details of these processes that connect the two countries and the issues of the advantages and disadvantages as well. In our paper we rely on literature data, private experiences, and the opinion of small scale farmers in Szabolcs-Szatmár-Bereg county, who have experience in employing laborers on a seasonal basis.